Macroeconomic Determinants Of Gross Domestic Product In Asean: The Role Of WTI Oil Prices And External Debt Ratio - Latif, Abdul; Hidayah, Zulfa Zakiatul; Hartati, Nani; Widiastuti, Widiastuti; Apriani, Erna (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study is to analyze the direct effect of the world oil price variable on the GDP variable, as well as the direct effect of world oil prices on the debt ratio, then the indirect relationship of world oil prices to GDP through the debt ratio. Methodology: The data analysis method used in the research is path analysis on the variables of world oil prices, GDP of ASEAN countries, and the ratio of foreign debt as an intervening variable. Results: The results found that the direct effect of the debt ratio on world oil prices had no effect, then the direct effect of the debt ratio on GDP had no effect, then the direct effect of WTI oil prices on GDP had no effect, and the results of the mediation dimension of WTI oil prices did not mediate the relationship between the debt ratio and GDP. Findings: The findings of the study show that macroeconomic factors, especially world oil prices and a country's debt ratio, do not affect a country's economic growth. Novelty: The gap in previous research makes novelty in the foreign debt ratio variable as a mediating dimension of the relationship between WTI oil prices and GDP.  Originality: This research discusses one of the fluctuating macroeconomic factors in its influence on the movement of a country's economy. Conclusion: Macroeconomic factors WTI world oil prices and a country's foreign debt ratio do not affect economic growth. Type of Paper: Quantitative research